(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
Study skills are critical to students’ achievement. The objective of this study is to assess the study skills of undergraduates. The Inventory of College Level Study Skills developed by Dennis H. Congos (2011), in which study skills were divided into six categories or subscales: textbook reading, note-taking, memorizing, test preparation, concentration, and time management, was adopted to collect data. The results of the analysis revealed that skimming for main ideas appeared to be the most frequently used reading technique among the participants; taking note in lectures is the most preferred skill. Regarding memory skills, the most popular skill was reviewing notes more than once or twice for exams and quizzes, and the least popular skill was using visual in notes such as sketches, mind maps, diagrams, charts, etc. In terms of test preparation skills, the most frequently-used skill was submitting homework assignments on time while the least favoured test preparation sub-skill was reviewing lecture note soon after classes. As for concentration skills, getting all study equipment ready for learning was considered the most important skill, while avoiding study in the evenings as much as possible was the least prioritized method. Accordingly, the researchers would recommend students be provided with suitable guidelines in order to practice good study skills.